2017
DOI: 10.1103/physics.10.127
|View full text |Cite
|
Sign up to set email alerts
|

Order on Command

Abstract: We explore a new mechanism for switching magnetism and superconductivity in a magnetically frustrated iron-based superconductor using spin-polarized scanning tunneling microscopy (SPSTM). Our SPSTM study on single-crystal Sr 2 VO 3 FeAs shows that a spin-polarized tunneling current can switch the Fe-layer magnetism into a nontrivial C 4 (2 × 2) order, which cannot be achieved by thermal excitation with an unpolarized current. Our tunneling spectroscopy study shows that the induced C 4 (2 × 2) order has charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Of particular interest are the so-called transition disks with large inner dust cavities (>20 au), (e.g. Espaillat et al 2014;van der Marel 2017). In this work, we use the term transition disk for any disk with a large cleared inner dust cavity (>20 au) as revealed by millimeter observations.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest are the so-called transition disks with large inner dust cavities (>20 au), (e.g. Espaillat et al 2014;van der Marel 2017). In this work, we use the term transition disk for any disk with a large cleared inner dust cavity (>20 au) as revealed by millimeter observations.…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate-mass black holes (IMBHs) of masses between 100−10 6 M⊙ (e.g., van der Marel 2004;Graham et al 2018) are however not as widely observed. Some studies argue that the accreting BHs in ultra-luminous X-ray sources could be IMBHs (e.g., Miller et al 2003;Sutton et al 2012;Caballero-Garcia et al 2018;Mezcua et al 2018b), based on the calculation of the BH mass from a cold thermal disc accreting at sub-Eddington rates.…”
Section: Introductionmentioning
confidence: 99%